Landscape in the South of France - Paul Huet (Wikimedia Commons, 1838)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Landscape in the South of France.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures